Revitalization at a Distance: Engaging Digital Archives for Language Reclamation. - Bowern, Claire; Hanson, Sue; Smith-Ali, Denise; Hayden, George (Transactions of the American Philosophical Society, 2024)
The article discusses the use of remote collaborations to aid in language reclamation projects with Australian Aboriginal and Torres Strait Islander communities. The focus is on collaborative work between linguists and communities to improve access to archival materials and create sketch grammars for Indigenous languages. The bootcamp model described in the article involves intensive training for undergraduate students, collaboration with community members, and the production of sketch grammars within a month. The program aims to make linguistic materials more accessible and valuable to communities while providing students with practical research experience.